Analysis of Factors Affecting the Establishment of Healthcare Associated Infections (HAIS) in Dr. Pirngadi Medan - Lingga, Evi Sofiani; Hakim, Lukman; Manurung, Kesaktian (Sari Mutiara Indonesia University Press, 2018)
Healthcare-associatedinfections (HAIs) are one of the causes of the increase in morbidity rate and mortality rate in a hospital. This infection becomes a new health problem. HAIs in a hospital is caused by bacteria, virus, fungi, or parasite which come from patients’ bodies and from exogenous factors, that is,from environment and polluted medical equipment. The objective of the research was to find out some factors which influenced the incidence of HAIs at RSUD dr. Pirngadi, Medan, in 2018. The research used observational analytic with case-control design. The samples were 69 patients with HAIs at RSUD dr. Pirngadi, Medan, in 2017. The result of multivariate analysis with logistic regression statistic test showed that some factors which influenced the incidence of HAIs were the use of antibiotics (p=0.032 < 0.05) and the number of treatment days (p=0.014 < 0.05). The factor which had the most dominant influence was the number of treatment days at OR-value = 5.516. The conclusion was that there as the influence of the use of antibiotics and the number of treatment days onthe incidence of HAIs. It is recommended that the hospital management pay attention to all aspects of infection in the hospital and prevent from infection which can endanger patients